Effects of flow velocity and impact angle on erosion-corrosion of an API-5 L X65 steel coated by plasma nitriding of hard chromium underlayer - M. Rameshk; M. Soltanieh; S.M. Masoudpanah (Journal of Materials Research and Technology, 2020)
In this study, the erosion-corrosion behavior of an API-5L-X65 steel coated by plasma nitriding of hard chromium underlayer has been investigated as a function of flow velocity (4, 5, 6, 7.5 m s−1) and impact angle (30°, 45°, 60°, 90°) by a slurry of 3.5 wt.% NaCl, and 3 wt.%SiO2. The structure and microstructure of coating were characterized by X-ray diffractometry and scanning electron microscopy techniques. The maximum of mass loss was at the impact angle of 45° which the degradation slightly decreased with the increase of impact angle. However, the maximum degradation of the CrN coated samples occurred at normal impact angle. The analysis of erosion-corrosion mechanism showed the erosion process was more effective than corrosion.